An unusual case of hepatic lymphoma with multiple epithelial malignancies - Anuj Khurana; Urmi Mukherjee; Nayana Patil (Wolters Kluwer Medknow Publications, 2018)
Primary hepatic mucosa-associated lymphoid tissue lymphoma (MALToma) is a rare entity. Its coexistence with other malignancies is even rarer. Only few case reports of its association with other malignancies mostly gastric and colon cancer have been published. We report a case of primary MALToma of liver in an unusual setting of dual solid malignancy.